Nutrition essentials a personal approach - Schiff, Wendy MS, RD (New York, NY McGraw-Hill Education, 2018)
The cover depicts the many baffling choices we face each day when we decide what to eat for meals and snacks. Do we choose foods simply based on convenience, taste, or cost? Or do we choose foods based on other factors, including the food's contribution to our nutritional needs and possible effects on our health and well-being? To make healthy food choices, we need to understand basic nutrition, including features of a healthy eating pattern and how what we eat can affect our health now and as we grow older. Nutritional Essentials: a personal approach provides this information in an easy-to-understand and engaging manner. There's no simple one-size-fits-all approach to good nutrition. However, the information in this textbook will help you understand how nutrients in foods affect your body, so you'll be able to evaluate your diet and improve it, if necessary
Food is more than something to eat -- Nutrition information: fact or fiction? -- Making more nutritious choices -- How food becomes you -- Carbohydrates: furl and fiber -- Lipids: Focusing of fats and cholesterol -- Proteins: Life's building locks -- Vitamins: nutrients that multitask --Key minerals, water, and the nonnutrient alcohol -- Nutrition for a healthy weight and fit body -- Nutrition for your life, environment, and world
Includes biographical references and index
Keywords: Human nutrition -- Textbooks